New Ixora Species from Bengal, Burma and the Nicobar Islands - Bremekamp, C. E. B. (Indian Forester, 1959)
This paper contains descriptions of 5 new species of Ixora, Ixora longibracteata and I. tigriomustax from Chittagong Hill Tracts, Ixora athroantha from Sukna, Bengal, I. rangonensis from Burma and I. tenuifolia from the Great Nicobars.